Kolaborasi Aktor Dalam Upaya Pengendalian Inflasi Daerah di Kota Palangka Raya - Farid Zaky Yopiannor (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Inflation is a strategic challenge faced by local governments in maintaining economic stability and public purchasing power. Palangka Raya City, as the capital of Central Kalimantan Province, experiences inflationary pressures due to its high dependence on external supplies and limited logistics infrastructure. This study aims to analyze the patterns of actor collaboration in regional inflation control by employing a qualitative approach with a case study design. Data were collected through in-depth interviews, limited participant observation, and document analysis, and then analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings reveal that collaboration among actors within the Regional Inflation Control Team (TPID) is formally structured but primarily dominated by key institutions such as Bank Indonesia and the City Government. The collaboration tends to be coordinative rather than deliberative, with limited engagement from local businesses and civil society actors. Using the collaborative governance framework, this study highlights the critical role of interaction quality, facilitative leadership, and integrated data systems in shaping effective collaboration. It recommends strengthening institutional capacity, enhancing public participation, and fostering cross-sectoral learning to support more sustainable and inclusive local inflation governance. Keywords: Regional Inflation; Actor Collaboration; Collaborative Governance; Local Economic Policy; Palangka Raya